DESIGN MESSAGE DA'WAH - Kamaluddin Ritonga (Hikmah, 2016)
Material message as one of the most important elements in missionary activity needs to bemanaged effectively to achieve the expected goals. In addition to in-depth mastery of thematerial, it needed accuracy in choosing the type of material that is appropriate to thesituation faced mad'u. Selection of materials is accurate, technique and determination ofthe appropriate steps to manage the message, must be based on several prinsifformulation, namely prinsif relevance, consistency, adequacy and prinsif hierarchy areguided by kai'idah-ka'idah ushuliyah about message management. For multiculturalsociety like Indonesia, preaching the message must necessarily adapted to the philosophyof national and state life. The diversity of race, culture, religion and language are the lawsin bumu. Propaganda message soothing and nurturing every difference is evidence ofMuhammad's prophethood as rahmatan lil 'alamin. Integrative propaganda messages intoone means to give birth to civilizations that tauhidik community in all aspects ofcommunitylife